The Six million reconsidered : Is the 'Nazi Holocaust' story a Zionist propaganda ploy? - Grimstad, William N.; Committee for Truth in History (Chapel Ascote, Southam : Historical Review Press, 1979)
V. 1. "In an examination of the Jewish genocide claim versus the disaster of the twentieth century".
The 'Anti-Semite' smear -- Zion's own 'six million' plans -- Breaking all vows, and other rites -- The tsarist pogrom myth -- Jews and organized crime -- 'One who survived' -- Some makers of the myth -- Jews and communism -- Summing up -- Epilogue in Palestine.
Includes bibliographical notes.
The Roger Griffin ComFas Collection
Keywords: Holocaust denial literature; Holocaust denial; Atrocities